Anisotropic abdominal aortic aneurysm replicas with biaxial material characterization. Issue 12 (December 2016) - Ruiz de Galarreta, Sergio; Antón, Raúl; Cazon, Aitor; Larraona, Gorka S.; Finol, Ender A.
Highlights: Manufacturing of non-uniform wall thickness and anisotropic AAA replicas. Biaxial testing of composite specimens. Mathematical model of composite and phantom specimens. Abstract: An Abdominal Aortic Aneurysm (AAA) is a permanent focal dilatation of the abdominal aorta at least 1.5 times its normal diameter. The criterion of maximum diameter is still used in clinical practice, although numerical studies have demonstrated the importance of other biomechanical factors. Numerical studies, however, must be validated experimentally before they can be clinically implemented. We have developed a methodology for manufacturing anisotropic AAA replicas with non-uniform wall thickness. Different composites were fabricated and tested, and one was selected in order to manufacture a phantom with the same properties. The composites and the phantom were characterized by biaxial tensile tests and a material model was fit to the experimental data. The experimental results were compared with data from the literature, and similar responses were obtained. The anisotropic AAA replicas with non-uniform wall thickness can be used in benchtop experiments to validate deformations obtained with numerical simulations or for pre-intervention testing of endovascular grafts. This is a significant step forward considering the importance of anisotropy in numerical simulations.